Effects of prolonged continuous computer gaming on physical and ocular symptoms and binocular vision functions in young healthy individuals - Lee, Ji-Woo; Cho, Hyun Gug; Moon, Byeong-Yeon; Kim, Sang-Yeob; Yu, Dong-Sik (PeerJ, 2019)
Background and Objective Addiction to computer gaming has become a social problem in Korea and elsewhere, and it has been enlisted as a mental health disorder by the World Health Organization. Most studies related to computer use and vision have individually assessed physical and ocular symptoms and binocular vision. Accordingly, the present study comprehensively assessed subjective physical and ocular symptoms and functions related to binocular vision after prolonged continuous computer gaming. This study aimed to investigate the effects of prolonged continuous computer gaming on physical and ocular health and visual functions in young healthy individuals. Methods Fifty healthy college students (35 male/15 female), aged 19–35 years old, were enrolled in this study. The inclusion criteria were no binocular vision problems and no reported history of ocular disease. Participants played continuously for 4 h from 6:00 to 10:00 p.m. Physical and ocular symptoms and visual functions such as convergence, accommodation, phoria, and the blink rate were assessed before and after continuous computer gaming for 4 h. Results Continuous computer gaming for 4 h resulted in convergence and accommodation disturbances and increased physical and ocular discomfort. Near phoria showed an exophoric shift, whereas distance phoria showed no change. Moreover, the accommodative and vergence facilities and blink rate were significantly decreased. All visual functions recovered to the baseline levels by the following morning. Discussion Our findings suggest that excessive and continuous computer gaming impairs visual functions and causes ocular and physical fatigue. Our findings further the understanding of the adverse effects of excessive computer use on physical and ocular health, and adequate breaks are necessary to reduce physical and visual discomfort during computer gaming.
Keywords: Physical health; Computer gaming; Prolonged game; Ocular health; Visual functions